The impact of corporate social responsibility initiative on sustainable livelihood capitals of cocoa farmers in Ghana : a case study of cocoa livelihood program in Ahafo Ano South District - Obeng, Godfred Adduow (2015)
The Cocoa Livelihood Programme (CLP), an initiative of corporate organizations in collaboration with the World Cocoa Foundation (WFC) in line with their corporate social responsibility (CSR), was introduced in Ghana by Solidaridad West Africa in the year 2009. This CSR initiative is to promote sustainable livelihoods of cocoa farmers. Qualitative research method of approach was used to examine the impact of the CLP on the livelihoods of participating cocoa farmers in the Ahafo Ano South District using the five capitals of the Sustainable Livelihood (SL) Framework. Two research questions were answered using thematic coding and analysis. The findings show that the cocoa livelihood programme (CLP) is impacting positively on the lives of cocoa farmers studied thereby contributing to their social, natural, physical, financial and human capital livelihoods. The CLP programme has resulted in sound environmental management and practices among the cocoa farmers, preventing landing degradation whiles yields from their cocoa cultivation has increased which is helping them to save some money for future use. The study also reveals some challenges to cocoa farmers, which inhibit the realization of sustainable livelihood, even with the achievements under the CLP. Cheating through weighing scale adjustments by cocoa purchasing clerks (PCs) confirms earlier researches. Providing legal support to get official registration of the lands of cocoa farmers and business trainings are some of the findings, which were not captured in the literatures reviewed under this study. The conditions that farmers needs to fulfil in order to participate in the CLP initiative should be reviewed as some farmers may be excluded from the program. Also there should be effective enforcement of laws to prevent illegal encroachment of farmlands by both gold seekers and timber merchants to enable cocoa farmers achieve sustainable livelihood.